BIODIESEL PRODUCTION: POTENTIAL AND FUTURE TRENDS – A REVIEW - Alhanif, Misbahudin (Universitas 17 Agustus 1945 (UNTAG) Semarang, 2023)
Biodiesel is a potential renewable energy that can reduce greenhouse gas (GHG) emissions and increase energy security. Biodiesel has been shown to have lower carbon emissions compared to petroleum diesel, and it can reduce GHG by as much as 86%. Governments around the world have set targets for renewable energy, with a specific focus on the use of biofuels like biodiesel. Biodiesel can be derived from various feedstocks such as animal lipids, vegetable oils, and waste oils. It can be made through the transesterification of triglyceride with ethanol or methanol. This reaction requires strong base catalysts, such as sodium hydroxide or potassium hydroxide, in order to produce methyl esters. The potential of biodiesel has led to advancements in its production, such as the use of enzymatic transesterification, novel feedstocks, and the optimization of production parameters. Additionally, various companies have ventured into biodiesel production with a range of business models and approaches.